Adsorption of nonionic surfactant on silica nanoparticles: structure and resultant interparticle interactions - Sharma, Kamendra P.; Aswal, Vinod K.; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2010)
Addition of nonionic surfactant, C(12)E(9), to an aqueous dispersion of charge stabilized silica nanoparticles renders particle aggregation reversible. In contrast, aggregation of the same silica particles in aqueous solutions is irreversible. We use a combination of small-angle X-ray scattering (SAXS) and contrast matching small-angle neutron scattering (SANS) to investigate interparticle interactions and microstructure in dispersions of silica particles in aqueous nonionic surfactant solutions. We show that the silica particles interact through a screened Coulombic interaction in aqueous dispersions; interestingly, this interparticle interaction is hard-sphere-like in surfactant solutions. In surfactant solutions, we show that the final surfactant-particle structure can be modeled as 14 micelles adsorbed (on average) on the surface of each silica particle. This gives rise to the short-range interparticle repulsion that makes particle aggregation reversible, and results in the hard sphere interparticle interaction potential. Finally, we show that adsorption of polyethylene imine on the surface of the silica particles prevents adsorption of surfactant micelles on the particle surface.

Assembly of polyethyleneimine in the hexagonal mesophase of nonionic surfactant: effect of pH and temperature - Sharma, Kamendra P.; Choudhury, Chandan Kumar; Srivastava, Sonal; Davis, Hilda C.; Rajamohanan, P. R.; Roy, Sudip; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2011)
We investigate the dispersion of a pH responsive polymer, polyethyleneimine, PEI, in a hexagonal (H(1)) mesophase of a nonionic surfactant, C(12)E(9), and water, at pH ranging from basic (pH = 12.8) to acidic (pH = 1). While the C(12)E(9)/H(2)O phase behavior is independent of pH, we demonstrate that, in the PEI/C(12)E(9)/H(2)O system, changing the pH influences PEI-C(12)E(9) interactions, and thus, influences the isotropic-H(1) phase transition. With decrease in pH, there is increasing protonation of the PEI chain, and consequently, the chain extends. We show, using a combination of SAXs, optical microscopy and visual experiments, that the inclusion of PEI in a 1:1 surfactant water mixture, lowers the hexagonal-isotropic transition temperature, T. At higher pH = 12.8 T(HI) shows a pronounced decrease from SO to 13 degrees C on addition of PEI, and the PEI/C(12)E(9)/H(2)O system forms a transparent gel. At pH = 1, we observe qualitatively different behavior and an opaque gel forms below T(HI)= 25 degrees C. The isotropic-H(1) transition, in turn, influences the phase separation of PEI chains from the C(12)E(9)/H(2)O system. 2D NMR ROESY data provides evidence that there are strong surfactant PEI interactions at high pH that significantly reduce at lower pH. The NMR data is in accord with molecular dynamics simulations that show that surfactants strongly aggregate with unprotonated PEI chains, but not with fully protonated chains; thus, in this system, the pH controls a cascade of microstructural organization: increasing pH decreases chain protonation and increases polymer-surfactant interactions, resulting in suppression of the isotropic-H(1) transition to lower temperatures, thus, influencing the phase separation of PEI from the surfactant/water system.

Accelerated in vitro model for occlusion of biliary stents: investigating the role played by dietary fibre - Surwase, Sachin; Balakrishnan, Harishankar; Acharya, Subrat K.; Makharia, Govind K.; Kumaraswamy, Guruswamy; Bhagavatula L. V. Prasad (BMJ Innovations, 2018)
ackground To develop a new accelerated in vitro model that has implications for investigating the mechanism of biliary stent occlusion and help in the development of new materials that can alleviate this problem. Methods We employ a combination of reconstituted animal bile, bacteria and cellulose fibres optimised to reproducibly generate accelerated occlusion of stents, and produce occlusions that closely mimic those found in clinical studies. Results Our model affords repeatable, highly accelerated occlusion (within 2–3 days, compared with between about a week to 2 months in previous models). Our results highlight the role of dietary fibre in blockage of stents and demonstrate their importance in the onset of occlusion. Conclusions This accelerated model may have implications for developing biliary stents with enhanced patency.

Aqueous dispersions of lipid nanoparticles wet hydrophobic and superhydrophobic surfaces - Kumar, Manoj; Kulkarni, Mayuresh A.; Chembu, Narendiran G.; Banpurkar, Arun; Kumaraswamy, Guruswamy (Soft Matter, 2018)
Efficient delivery of aqueous sprays to hydrophobic surfaces is the key technological challenge in a wide variety of applications, including pesticide delivery to plants. To account for losses due to bouncing of pesticide sprays off hydrophobic leaf surfaces, a large excess of pesticide is typically employed, resulting in environmentally hazardous run-offs that contaminate soil and ground water. We demonstrate that aqueous dispersions of glycerol monooleate nanoparticles, called cubosomes, wet hydrophobic and superhydrophobic surfaces and adhere to them. Cubosomes comprise glycerol monooleate lipid molecules self-assembled into a double diamond cubic phase, that form stable aqueous dispersions that are sterically stabilized using amphiphilic block copolymers. We use high speed imaging to monitor the spreading and retraction of aqueous drops impinged on model hydrophobic substrates and on superhydrophobic lotus leaves. We show that cubosomes diffuse to hydrophobic substrates and reorganize to form a thin, approximate to 2 nm adsorbed lipid layer during the millisecond time scales that characterize drop impact. This adsorbed film drastically reduces the water contact angle, transforming the hydrophobic surface to hydrophilic, thus facilitating retention of the aqueous drop on the surface. Aqueous drops of cubosomes impinged at low velocities on inclined natural superhydrophobic lotus leaf surfaces do not roll off, unlike drops of water or surfactant solutions. When sprayed on inclined lotus leaves, corresponding to the case of high velocity drop impingement, cubosome dispersions form a continuous wetting film. Our results have important implications for efficient, environment-friendly delivery of pesticide sprays.